Students as co-producers: Establishing the conditions for a successful partnership within an undergraduate research scheme - Dargahi, Shilan; Horne, Jessica; Smith, Susan (International Journal for Students as Partners, 2024)
To engage students with academic research is recognised as a high-impact activity that supports the development of valuable critical thinking skills. Various approaches have been developed to promote student research both in and outside the curriculum. By incorporating the perspectives of both students and academics, this qualitative study evaluates the extent to which a research partnership is formed through an institutional research scheme called the Junior Research Associate. Our findings indicate that it is critical to move beyond the entrenched academic hierarchies of supervisor/supervisee to develop a negotiated research relationship. Challenges identified include the short timeframe to establish the conditions for successful partnership and differential expectations of partners at the outset of the scheme. It is also important to safeguard against such initiatives being instrumentalised by academics seeking to further their personal research agenda. The findings help to inform strategies to scale up such initiatives.